Β-glucan release from fungal and plant cell walls after simulated gastrointestinal digestion. (August 2021) - Colosimo, Raffaele; Mulet-Cabero, Ana-Isabel; Cross, Kathryn L.; Haider, Kathrin; Edwards, Cathrina H.; Warren, Frederick J.; Finnigan, Tim J.A.; Wilde, Peter J.
Graphical abstract: Highlights: Plants can release β-glucans from the cell walls during gastrointestinal digestion. Oat and barley bran release β-glucans in both uncooked and cooked treatment. Cooking promotes β-glucans release in mycoprotein but not in white button mushrooms. Pancreatic enzymes facilitate β-glucan release. Abstract: β-glucans are soluble fibre found in plant and fungal cell walls, which are linked with reduced serum lipid levels. This study investigates the β-glucan release from two fungal samples (mycoprotein and white button mushroom) compared with two plant samples, oat and barley bran. Our results indicate no β-glucan release after the simulated gastrointestinal digestion of the uncooked fungal samples. In contrast, following cooking and digestion, β-glucans were released from the mycoprotein matrix. Pancreatic enzymes facilitated the solubilisation of β-glucans. Protein and carbohydrate digestion appeared independent of β-glucan release in both uncooked and cooked samples. Conversely, the viscosity increased in the samples that showed a significant release of β-glucans at the end of gastrointestinal digestion. Structural analysis by scanning electron microscopy showed changes in the uncooked and cooked samples before and after digestion. This study shows for the first time the different behaviour in β-glucan release from fungal and plant samples.